Attitudes to global trade and TTIP in Germany and the United States - Bluth, Christian (Gütersloh, 2016)
"Everyone can benefit from free trade – according to the promise made at the start of negotiations on the Transatlantic Trade and Investment Partnership in 2013. But critical voices have been piling up since then. A new survey examines the attitudes toward free trade and the TTIP on both sides of the Atlantic."